When They Call, Will They Come? A Contextually Responsive Approach for Engaging Multistressed Families in an Urban Child Mental Health Center: A Randomized Clinical Trial. (September 2015) - Stern, Susan B.; Walsh, Margaret; Mercado, Micaela; Levene, Kathryn; Pepler, Debra J.; Carr, Ashley; Heppell, Allison; Lowe, Erin
Objective: This study examines the effect of an ecological and contextually responsive approach, during initial intake call, on engagement for multistressed families seeking child mental health services in an urban setting. Methods: Using a randomized design, parents were allocated to phone Intake As Usual (IAU) or Enhanced Engagement Phone Intake (EEPI). IAU consisted of a lengthy mandated standardized phone intake interview. EEPI, wrapped around the standard intake, was a flexible approach, attuning to the parent's concerns, help-seeking experience, and stressors and incorporating problem-solving and motivational interviewing. Results: Controlling for child gender, child age, income, and marital status, parents in the EEPI condition were 3 times more likely to attend their initial face-to-face agency appointment and subsequent treatment services. Conclusions: This study contributes to building the evidence base for early engagement approaches responsive to families' broader ecological context to ensure that vulnerable children and families access and receive benefits of treatment.